2009
DOI: 10.1017/s0965539509990040
|View full text |Cite
|
Sign up to set email alerts
|

Third Stage Practices and the Neonate

Abstract: The third stage of labour is defined as the period following the completed delivery of the newborn until the completed delivery of the placenta and its attached membranes. Whilst to the exhausted labouring woman this stage may be an afterthought, it is a crucial time for fetal-to-neonatal transition. Major changes in anatomy and physiology occur in both mother and baby. It has also been described as ‘potentially the most hazardous part of childbirth, largely due to the risk of postpartum haemorrhage (PPH) on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Saigal found significant increases in both neonatal hyperbilirubinaemia and polycythaemia in infants randomized to delayed vs early cord clamping. 4 A subsequent systematic review and meta-analysis found a non-statistically significant increase in polycythaemia among infants in whom cord clamping was delayed, although the condition appeared benign. 4 A recent Cochrane review 5 concluded that although later cord clamping increases the risk of jaundice requiring phototherapy, it advantages the term infant by improving iron stores.…”
Section: -10s 30-45smentioning
confidence: 99%
See 3 more Smart Citations
“…Saigal found significant increases in both neonatal hyperbilirubinaemia and polycythaemia in infants randomized to delayed vs early cord clamping. 4 A subsequent systematic review and meta-analysis found a non-statistically significant increase in polycythaemia among infants in whom cord clamping was delayed, although the condition appeared benign. 4 A recent Cochrane review 5 concluded that although later cord clamping increases the risk of jaundice requiring phototherapy, it advantages the term infant by improving iron stores.…”
Section: -10s 30-45smentioning
confidence: 99%
“…Expectant management excludes prophylactic drugs, the cord is neither clamped nor cut early, and the placenta is expelled by maternal effort. 4 Active management traditionally involves routine prophylactic administration of a uterotonic agent, early cord clamping and cutting, and controlled cord traction. The administration of uterotonics reduces the risk of postpartum haemorrhage, a complication of childbirth which accounts for almost one quarter of all maternal deaths worldwide.…”
Section: Modern Obstetric Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Initially introduced as part of active management of the third stage of labour to reduce the risk of post-partum hemorrhage [1], the safety of early cord clamping was soon questioned [2] and investigated [3]. The finding that depriving the neonate of a volume of blood [4] resulted in anaemia and iron deficiency six weeks later [5] was not surprising but only recently this anaemia and iron deficiency has been shown to have more significant long term adverse consequences [6].…”
Section: Introductionmentioning
confidence: 99%